Pengembangan E-LKPD Berbasis Problem Based Learning Berbantuan Quizizz untuk Meningkatkan Hasil Belajar - Meriyenti zull; Amar Salahuddin; Estuhono (Jurnal Muara Pendidikan, 2026)
This study aims to develop an e-LKPD based on Problem Based Learning (PBL) integrated with the Quizizz application. This development is a response to the low learning outcomes and the lack of interactive media that can trigger active participation and critical thinking of grade XI students in Economics material, especially National Income. Using the ADDIE model which is an acronym for Analysis, Design, Development, Implementation, and Evaluation. This study involved students of SMAN 10 Tebo. Data were collected through observation, interviews, expert validation questionnaires, practicality, and learning outcome tests. The results showed that this e-LKPD was suitable for use with a very good level of validity (above 85% for language, content, and media). This media was also considered very practical by teachers (95%) and students (81.33%). The effectiveness aspect was seen from the increase in students' average score from 76.60 (pretest) to 81.29 (posttest), indicating an increase of 6.12%. From the results of this research analysis, it can be recommended that PBL-based e-LKPD assisted by Quizizz is proven to be effective, valid, and practical in improving learning outcomes in the Economics subject on the National Income material.